New assay method based on Raman spectroscopy for enzymes reacting with gaseous substrates. (16th January 2019) - Kawahara‐Nakagawa, Yuka; Nishikawa, Koji; Nakashima, Satoru; Inoue, Shota; Ohta, Takehiro; Ogura, Takashi; Shigeta, Yasuteru; Fukutani, Katsuyuki; Yagi, Tatsuhiko; Higuchi, Yoshiki
Abstract: Enzyme activity is typically assayed by quantitatively measuring the initial and final concentrations of the substrates and/or products over a defined time period. For enzymatic reactions involving gaseous substrates, the substrate concentrations can be estimated either directly by gas chromatography or mass spectrometry, or indirectly by absorption spectroscopy, if the catalytic reactions involve electron transfer with electron mediators that exhibit redox‐dependent spectral changes. We have developed a new assay system for measuring the time course of enzymatic reactions involving gaseous substrates based on Raman spectroscopy. This system permits continuous monitoring of the gas composition in the reaction cuvette in a non‐invasive manner over a prolonged time period. We have applied this system to the kinetic study of the [NiFe] hydrogenase from Desulfovibrio vulgaris Miyazaki F. This enzyme physiologically catalyzes the reversible oxidation of H2 and also possesses the nonphysiological functions of H/D exchange and nuclear spin isomer conversion reactions. The proposed system has the additional advantage of enabling us to measure all of the hydrogenase‐mediated reactions simultaneously. Using the proposed system, we confirmed that H2 (the fully exchanged product) is concomitantly produced alongside HD by the H/D exchange reaction in the D2 /H2 O system. Based on a kinetic model, the ratio of the rate constants of the H/D exchange reaction ( k ) at the active site and product release rate ( k out ) was estimated to be 1.9 ± 0.2. The proposed assay method based on Raman spectroscopy can be applied to the investigation of other enzymes involving gaseous substrates.